2023
DOI: 10.1021/acscatal.3c01340
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the Fate of α-Fe2O3 in CO2 Hydrogenation through Combined Time-Resolved In Situ Characterization and Microkinetic Analysis

Abstract: CO2 hydrogenation over Fe-based catalysts is a promising pathway to mitigate emissions of this greenhouse gas and provides a possibility for crude-oil-free production of chemicals and fuels. Understanding of (i) the role of crystalline phases or/and surface species in the working catalysts, (ii) the factors affecting their formation under reaction conditions, and (iii) the kind and reactivity of surface precursors of gas-phase products is vital for controlling the efficiency of CO2 hydrogenation. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…By employing time-resolved in situ techniques (XRD, XPS, and Raman), very recently, our group contributed to revealing deactivation mechanisms of Febased catalysts in CO 2 -FTS. [22] The observed decrease in CO 2 conversion and changes in product selectivity with time-onstream cannot be explained by the re-oxidation of Fe x C y . Instead, in situ XPS and Raman confirmed the formation of carbon depositions that negatively affect the activation of H 2 / CO 2 and the formation of active intermediates as rationalized by transient kinetic studies.…”
Section: Active Phases and Their Spatial Distribution Upon Catalyst R...mentioning
confidence: 93%
“…By employing time-resolved in situ techniques (XRD, XPS, and Raman), very recently, our group contributed to revealing deactivation mechanisms of Febased catalysts in CO 2 -FTS. [22] The observed decrease in CO 2 conversion and changes in product selectivity with time-onstream cannot be explained by the re-oxidation of Fe x C y . Instead, in situ XPS and Raman confirmed the formation of carbon depositions that negatively affect the activation of H 2 / CO 2 and the formation of active intermediates as rationalized by transient kinetic studies.…”
Section: Active Phases and Their Spatial Distribution Upon Catalyst R...mentioning
confidence: 93%
“…Further contributions from Diego et al identified strongly adsorbed carboxylate species on spent catalyst surfaces, indicating potential obstacles to further catalyst carburization during FTS due to their strong interaction with iron oxide sites. Additionally, findings from Yang et al’s in situ Raman and pseudo in situ XPS analyses highlighted that carbon deposits impede the catalyst’s ability to generate surface adsorbed species from H 2 and CO 2 . A proposed solution from Han et al involved introducing H 2 O into the syngas, expediting the removal of surface carbon deposits and thereby shortening the reaction induction period by exposing more active sites .…”
Section: Probing Reaction-induced Structural Changes Of Iron Phasesmentioning
confidence: 99%
“…Most recently, Prof. Kondratenko’s group investigated the phase transformation of α-Fe 2 O 3 , synthesized via chemical precipitation from iron nitrate nonahydrate, employing a series of time-resolved in situ Raman, in situ XRD, and in situ NAP-XPS methodologies . Their results echoed our findings, observing the evolution pattern of Fe 2 O 3 → Fe 3 O 4 → Fe(0) → Fe 5 C 2 /Fe 3 C. However, the catalyst exhibited selectivity loss to hydrocarbons over time on stream.…”
Section: Steering the Structural Evolution: The Role Of Reactive Envi...mentioning
confidence: 99%
“…6–9 Thermal catalytic hydrogenation of CO 2 to produce high value-added chemicals (such as hydrocarbons) is one of the most profitable pathways. 10–14 However, it is still extremely difficult to achieve the transformation of CO 2 into hydrocarbons by a one-step reaction due to the chemical inertness of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium, Na, was widely used as a promotor to improve the ability of iron carbide to resist the oxidation of H 2 O and CO 2 , as well as the reduction of H 2 , leading to the improvement of selectivity to the desired products. 11,26 For example, a multifunctional Na-Fe 3 O 4 /HZSM-5 catalyst was reported to convert CO 2 into a gasoline fuel with a selectivity up to 78% for all hydrocarbons while only 4% for methane. 12 Another kind of alkali, potassium, K, was reported to be able to enrich the surface basicity of the catalyst and accelerate the carburization of Fe-based catalysts to form active iron carbides, thus assisting in CO 2 conversion.…”
Section: Introductionmentioning
confidence: 99%